THEORETICAL AND PRACTICAL BASIS OF MODERNIZING THE SYSTEM OF LABOR ORGANIZATION AND MANAGEMENT AT INDUSTRIAL ENTERPRISES (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The article extensively covers issues of improving the system of labor organization and management at industrial enterprises. It analyzes the legal, economic, social, and spiritual-psychological foundations of labor organization. The effective use of labor resources, increasing production productivity, strengthening labor discipline, and modernizing the management system are considered urgent problems. Also, ways to increase labor productivity through the introduction of digital technologies in the industrial sectors of Uzbekistan and the application of innovative management methods will be substantiated. The work emphasizes the need to develop the light industry, increase the potential of employees, and scientifically organize labor processes based on Presidential decrees and state programs. The research results serve to increase the efficiency of industrial enterprises, the rational use of human capital, and the strengthening of the competitiveness of enterprises.